2022
DOI: 10.3390/biomedicines10081772
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Assessment of C57BL/6 Hippocampi after Non-Selective Pharmacological Inhibition of Nitric Oxide Synthase Activity: Implications of Seizure-like Neuronal Hyperexcitability Followed by Tauopathy

Abstract: Nitric oxide (NO) is a small gaseous signaling molecule responsible for maintaining homeostasis in a myriad of tissues and molecular pathways in neurology and the cardiovasculature. In recent years, there has been increasing interest in the potential interaction between arterial stiffness (AS), an independent cardiovascular risk factor, and neurodegenerative syndromes given increasingly epidemiological study reports. For this reason, we previously investigated the mechanistic convergence between AS and neurode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…In another study, RPL8 was signi cantly increased in mouse models of pentylenetetrazole (PTZ)-induced epilepsy [47] . Several studies have suggested the association of RPS23 with neurodevelopmental disorders [48][49][50] . In addition, RPL15 is differentially expressed across all brain regions in Parkinson's Disease and is thought to be closely associated with other brain diseases [51] .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, RPL8 was signi cantly increased in mouse models of pentylenetetrazole (PTZ)-induced epilepsy [47] . Several studies have suggested the association of RPS23 with neurodevelopmental disorders [48][49][50] . In addition, RPL15 is differentially expressed across all brain regions in Parkinson's Disease and is thought to be closely associated with other brain diseases [51] .…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between proteome or metabolome changes and drug perturbation was also explored in some of the selected papers. A proteomic snapshot of progressive molecular signatures was carried out in hippocampal mice tissue after pharmacological inhibition of nitric oxide synthase activity [46], whilst a proteomic analysis highlighted the effects of chitosan hydrogel supplemented with metformin on the neural differentiation of stem cells, with the final aim of employing them in the construction of biomimetic scaffolds for disease treatment [47].…”
mentioning
confidence: 99%